2017
DOI: 10.1186/s12913-017-2651-z
|View full text |Cite
|
Sign up to set email alerts
|

Telephone triage utilization among patients with limited English proficiency

Abstract: BackgroundCommunication between patients with limited English proficiency (LEP) and telephone triage services has not been previously explored. The purpose of this study was to determine the utilization characteristics of a primary care triage call center by patients with LEP.MethodsThis was a retrospective cohort study of the utilization of a computer-aided, nurse-led telephone triage system by English proficiency status of patients empaneled to a large primary care practice network in the Midwest United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…One study of adults in an academic primary care practice showed that patients with LEP who received advice from a nurse-led telephone triage system were more likely to receive recommendations for higher acuity of care and were more likely to disagree with recommendations that were given. 9 Future research should include primary care patients utilizing telephone advice and presenting to the clinic for all visits as well as those patients presenting to the emergency room. The latter group may be particularly at risk and may face the most barriers because they may rarely utilize primary care services.…”
Section: Clinic Openmentioning
confidence: 99%
See 2 more Smart Citations
“…One study of adults in an academic primary care practice showed that patients with LEP who received advice from a nurse-led telephone triage system were more likely to receive recommendations for higher acuity of care and were more likely to disagree with recommendations that were given. 9 Future research should include primary care patients utilizing telephone advice and presenting to the clinic for all visits as well as those patients presenting to the emergency room. The latter group may be particularly at risk and may face the most barriers because they may rarely utilize primary care services.…”
Section: Clinic Openmentioning
confidence: 99%
“…8 Less is known specifically about access to primary care pediatric telephone advice for families who do not usually speak English at home; however, one study of calls to a nurse triage system showed that adult LEP patients were more likely to receive recommendations for higher acuity care and were more likely to disagree with recommendations from the nurse. 9 Our primary objective was to characterize the use of pediatric primary care telephone advice by families whose usual language spoken at home is not English. Specifically, we sought to determine if families whose usual language is not English are less likely to seek or obtain telephone advice, if language is a barrier to obtaining telephone advice, and if these barriers affect care-seeking behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within urgent care, different types of services utilise telephone-based digital triage, including national or regional help-lines, out-of-hours centres and emergency care providers. Examples of telephone-based services include England's National Health Service (NHS) 111 service, Scotland's NHS 24 service, Denmark's medical help line (MH1813), Australia's HealthDirect and the MayoClinic telephone service based in the USA [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the impact and outcomes is fraught, as many studies are dated; sparse; variable for time periods; reflect different health systems; focus on differing service availability (during work hours or after hours); and, differ in triage models (nursing vs medical staff). Various studies on the topic have been conducted across a range of health systems and time periods though, including the United Kingdom, Canada, Switzerland, the United States, the Netherlands, Pakistan, Denmark, and Australia …”
Section: Introductionmentioning
confidence: 99%